THE EFFICACY OF AVOCADO, MUNG BEAN SPROUTS, AND HOLY BASIL HERB COMBINATION (JAMU ATOKE) ON THE HEALTH AND REPRODUCTIVITY OF ADULT FEMALE RATS - Andriyanto Andriyanto Andriyanto; Leliana Nugrahaning Widi; Hamdika Yendri; Kharisma Mardathilah; Diky Yuliansah; Firda Agustin; Aulia Andi Mustika; Wasmen Manalu (Universitas Syiah Kuala, 2022)
The purpose of this study was to examine the efficacy of a herbal combination of avocado, mung bean sprouts, and holy basil (Jamu ATOKE) in optimizing the reproductive health of adult female rats. Eighteen female Sprague Dawley rats aged 9-10 weeks old weighing around 180-250 g, and had not been pregnant previously were equally and randomly divided into 3 groups: one control group and two treatment groups (n= 6 rats per group). The treatment groups received Jamu ATOKE with a concentration of 2.5 and 5%, respectively. Jamu ATOKE was added to the drinking water and consumed by the rats for 30 days prior to pregnancy. Reproductivity (pregnancy success, estrogen and progesterone hormone concentrations), and health performance (body weight gain, food, and water consumption, motor activity, red blood cell (RBC) count, white blood cell (WBC) count and differentials, SGPT, SGOT, ureum, and creatinine) of rats were observed. The results showed that groups receiving the Jamu ATOKE had better reproductive and health performance compared to those of the control group. The administration of Jamu ATOKE can significantly increase the concentration of estrogen and progesterone in rats (P0.05). It can also improve the fertility and health of the female rats prior to pregnancy.